Evaluation of a sequencing batch reactor sewage treatment rig for investigating the fate of radioactively labelled pharmaceuticals: Case study of propranolol. (1st January 2016) - Popple, T.; Williams, J.B.; May, E.; Mills, G.A.; Oliver, R.
Abstract: Pharmaceuticals are frequently detected in the aquatic environment, and have potentially damaging effects. Effluents from sewage treatment plants (STPs) are major sources of these substances. The use of sequencing batch reactor (SBR) STPs, involving cycling between aerobic and anoxic conditions to promote nitrification and denitrification, is increasing but these have yet to be understood in terms of removal of pharmaceutical residues. This study reports on the development of a laboratory rig to simulate a SBR. The rig was used to investigate the fate of radiolabelled propranolol. This is a commonly prescribed beta blocker, but with unresolved fate in STPs. The SBR rig (4.5 L) was operated on an 8 h batch cycle with settled sewage. Effective treatment was demonstrated, with clearly distinct treatment phases and evidence of nitrogen removal. Radiolabelled 14 C-propranolol was dosed into both single (closed) and continuous (flow-through) simulations over 13 SBR cycles. Radioactivity in CO2 off-gas, biomass and liquid was monitored, along with the characteristics of the sewage. This allowed apparent rate constants and coefficients for biodegradation and solid:water partitioning to be determined. Extrapolation from off-gas radioactivity measurements in the single dose 4-d study suggested that propranolol fell outside the definitions of being readily biodegradable (DegT50 = 9.1 d; 60% biodegradation at 12.0 d). During continuous dosing, 63–72% of propranolol was removed in the rig, but less than 4% of dose recovered as 14 CO2, suggesting that biodegradation was a minor process ( K biol (M) L kg d −1 = 22–49) and that adsorption onto solids dominated, giving rise to accumulations within biomass during the 17 d solid retention time in the SBR. Estimations of adsorption isotherm coefficients were different depending on which of three generally accepted denominators representing sorption sites was used (mixed liquor suspended solids, reactor COD or mass of waste activated sludge). With further development and evaluation, the rig developed for simulating SBR processes has potential to be used for informing better environmental risk assessments for those pharmaceuticals showing ambiguous results in field fate studies. Graphical abstract: Highlights: A lab rig was developed to simulate sewage treatment in a sequencing batch reactor. Radiolabelled propranolol was dosed in the rig and fate studies undertaken. Limited biodegradation was seen, with radioactive accumulations on MLSS. "Apparent" values of K d and K biol were derived for environmental risk assessments. Lab simulation rigs using radiolabelled pharmaceuticals may have wider applications.